Screening of exotic banana accessions for their resistance to fusarium wilt race 1 and tropical race 4 in India - Thangavelu, R.; Loganathan, M.; Backiyarani, S.; Saraswathi, M. S.; Uma, S.; Edwinraj, E.; Durai, P.; Nithya, B.; Roux, Nicolas; Selvarajan, R. (Nature Portfolio, 2025)
Fusarium wilt, caused by the soil-borne pathogen Fusarium oxysporum f. sp. cubense (Foc), is one of the most destructive diseases affecting global banana production. Foc Race 1 (Foc R1) and Tropical Race 4 (Foc TR4) are particularly destructive and lethal, impacting both Cavendish and local commercial cultivars. Deploying resistant varieties is crucial for managing this disease in commercial cultivation. This study evaluated 99 exotic banana accessions from the International Transit Centre (ITC), Belgium, representing diverse genomic groups to identify resistant sources within the banana gene pool. The accessions were assessed against both Foc R1 and Foc TR4 under glasshouse and hotspot field conditions. Disease severity was assessed using rhizome discoloration at harvest. The results of the study indicated significant variation across genome groups, test conditions, and Foc races (P < 0.001). Out of 99 accessions, 63 exhibited either an increase or decrease in resistance level in accessions between the test conditions, while 36 remained stable. Similarly, 68 accessions showed shifts between the tested races, while 31 remained stable. In the field evaluation of Foc R1, 19 accessions were immune, 13 highly resistant, and 17 were resistant, whereas in the glasshouse, only one accession was immune, nine were highly resistant, and 46 were resistant, indicating a greater resistance response under controlled conditions. For Foc TR4, 18 accessions were immune, nine highly resistant, and 19 were resistant in the field, whereas in the glasshouse, one was immune, 30 were highly resistant, and 50 were resistant, demonstrating a notable shift in resistance levels between environments. Some of these banana accessions show potential for direct commercial deployment in Fusarium wilt hot spot areas and/or could be used to identify resistant genes to further improve commercial cultivars through genetic engineering or gene editing techniques.